Numerical Simulations as Tool to Predict Chemical and Radiological Hazardous Diffusion in Case of Nonconventional Events - J.-F. Ciparisse; A. Malizia; L. A. Poggi; O. Cenciarelli; M. Gelfusa; M. C. Carestia; D. Di Giovanni; S. Mancinelli; L. Palombi; C. Bellecci; P. Gaudio (Modelling and Simulation in Engineering)
CFD (Computational Fluid Dynamics) simulations are widely used nowadays to predict the behaviour of fluids in pure research and in industrial applications. This approach makes it possible to get quantitatively meaningful results, often in good agreement with the experimental ones. The aim of this paper is to show how CFD calculations can help to understand the time evolution of two possible CBRNe (Chemical-Biological-Radiological-Nuclear-explosive) events: (1) hazardous dust mobilization due to the interaction between a jet of air and a metallic powder in case of a LOVA (Loss Of Vacuum Accidents) that is one of the possible accidents that can occur in experimental nuclear fusion plants; (2) toxic gas release in atmosphere. The scenario analysed in the paper has consequences similar to those expected in case of a release of dangerous substances (chemical or radioactive) in enclosed or open environment during nonconventional events (like accidents or man-made or natural disasters).